Internationalization of Halal Product Assurance Standards in Indonesia in Ensuring Consumer Rights: Implications and Orientation - Wibowo, Dwi Edi; Soeharto, Achmad; Kunantiyorini, Anik; Prematura, Aditya Migi; Begishev, Ildar; Taufiq (Universitas Negeri Surabaya, 2024)
Halal product assurance is part of consumer rights that ensures consumers receive a legal guarantee for a product that has been certified halal. In Indonesia, there are efforts to internationalize halal product assurance standards through cooperation with other countries. This research aims to analyze the legal implications and orientation related to the internationalization of halal product assurance standards in Indonesia with other countries. This research is a normative legal study that emphasizes conceptual, legislative, and historical approaches. The research results indicate that the internationalization of halal product assurance standards in Indonesia can have positive implications, such as the adoption of Indonesian halal regulations and standards by other countries, increased cooperation with both Muslim-majority and non-Muslim countries, and enhanced competitiveness of Indonesian products in the global halal industry market, particularly from the small, micro, and medium enterprise sector. Future orientation in the internationalization of halal product assurance standards in Indonesia can be achieved through strengthening cooperation with non-Muslim countries in terms of technology transfer, and with Muslim countries to improve the quality of halal certification and strengthen their position in the global halal market. This research offers novelty in the form of international collaboration and legal implications that can have a wide-ranging impact, especially on the competitiveness of Indonesian products in the global halal market. This research recommends a revision of Government Regulation No. 39 of 2021 concerning the Implementation of the Halal Product Assurance Sector to formulate more optimal regulations regarding international cooperation in halal product assurance standards in Indonesia. Keywords: Consumer Rights, Internationalization, Halal Product Assurance, Cooperation.